Pengaruh Investasi, Tenaga Kerja dan Pendidikan Terhadap Pertumbuhan Ekonomi Dalam Perspektif Ekonomi Islam - Nisya Fauzi; Wahyu Iryana; Agus Kurniawan (Universitas Islam Negeri Sumatera Utara, 2026)
Regional economic growth is influenced not only by output expansion but also by the effective utilization of production factors. Bandar Lampung City, as the economic center of Lampung Province, has experienced fluctuating growth, requiring an analysis of its determinants. This study examines the effects of investment, labor, and education on economic growth from an Islamic economics perspective during 2012–2024. A quantitative associative approach was applied using secondary time-series data from the Central Bureau of Statistics (BPS). The data were analyzed using multiple linear regression with the Ordinary Least Square (OLS) method after classical assumption tests. The results show that labor has a negative and significant effect, while investment and education have positive but insignificant effects. Simultaneously, all variables significantly influence economic growth. These findings emphasize the importance of the quality and effectiveness of production factors in promoting equitable regional economic growth.